Staining beverages and cigarette smoke on composite resin and human tooth fluorescence by direct spectrometry - Da Silva, Tânia Mara [UNESP]; Da Silva, Natália Yamachita [UNESP]; Gonçalves, Lucélia Lemes [UNESP]; Alves, Leandro Procópio; Fernandes, Adjaci Uchoa; De Paiva Gonçalves, Sérgio Eduardo [UNESP] (Jaypee Brothers Medical Publishing, 2017)
Introduction: This study evaluated the fluorescence intensity (FI) of different brands of composite resins (CRs) and compare those values with the FI of human tooth, under the action of cigarette smoke (CI), coffee (CA), and soft drink (CO), measured by direct spectrometry. Materials and methods: A total of 30 specimens of each brand (Filtek Z350, Esthet-X, Amelogen, Durafill) were made. Others 30 tooth specimens (3 mm/diameter) were obtained from human molars using a trephine bur. The specimens were randomly divided into three groups (n = 10), according to substances: CI, CA, CO. The FI was directly measured using an optic fiber associated with a spectrometer and was measured at baseline and after staining. Data were submitted to Kruskal-Wallis, Dunnett, and Dunn tests. Results: Staining influenced FI mean values among CRs and between those with human tooth. Z showed the closest FI mean values of tooth after staining. Conclusion: Staining beverages and cigarette smoke negatively influenced on FI of CR and human tooth. Clinical significance: The study shows darkening treatments influenced on the fluorescent property of the dental tissues and restorative materials according to the direct spectrometry analysis.
Keywords: Composite resins; Dye; Enamel; Fluorescence